Tense in the Principles of Semantics - Mouheb Aldeen, Deeaa Hussin (Arab Journal for Sciences and Research Publishing, 2019)
“Tense in the Principles of Semantics” is a study that discusses tense in one of rhetoric, namely semantics. The significance of this research stems from the fact that it sheds light on tense as an important aspect of language. It also discusses the influence of tense on the formulation and the application of a significant number of the principles of semantics. The present research, then, examines the impact of tense on formulating some of the rules of semantics and seeks to extract the rhetoric meaning that is built on tense in these rules. The researcher has adopted the analytical, descriptive methodology of this research, which is structured in four parts, an introduction, two body analyses and a conclusion. The findings revealed that the syntactic tense was in the verb form, the grammatical tense – which can be deduced from the context- was in the structure, and that the rhetoric tense was in the rhetoric meaning that tense enacts in the structure. It was also found that tense interferes in formulating many principles in semantics. In addition, the study found that tense has a clear impact on recognising the event, since event recognition is bound to tense recognition. Tense also interfered in what rhetoricians know as going beyond the surface to serve other rhetorical purposes. We might express the future using the past tense to reflect the certainty that something will happen. Language also expresses the past using the present tense for rhetorical purposes, like recalling the past event and visualising it as a realty for the addressee, and to show repetition of the verb. Furthermore, the future can be represented using the subject nominalisation or the object nominalisation with the intention of nearing the occurrence of some event in order to warn form it.
Keywords: Morphological Time; Syntactic Time; Rhetorical Time; Consideration of Context; Departure from the Apparent Meaning